The Political And Economic State Of South Africa In 2017: A Case Study Of Entrepreneurs Within In Disadvantaged Community In Kwa- Zulu Natal - Dabideen, Varsha (The IIE, 2017)
This thesis explores the daily life experiences, perceptions and challenges of entrepreneurs’ living in the Yellowwood Park community, in the South of Durban. This research will delve into the consequences of the political and economic state of South Africa by analysing (a) how political corruption has affected small business owners, (b) how the weakening of the rand has impacted small business owners, and (c) entrepreneurs’ views and opinions about the government and the state of the country. The thesis took the stance of the interpretivist paradigm, specifically the ontological position of interpretivism because there is a fundamental difference between people and objects because people are continually changing and being influenced by their environment, whereas objects are not. The study makes use of the case study methodology to investigate and gain an in-depth understanding of the lives of the entrepreneurs’. Interviews were used as the data collection tool for this study. The data analysis was performed using a thematic analysis along with using a theoretical framework to deduce and explore the research questions. The study concluded by showing that the entrepreneurs in Yellowwood Park are experiencing difficulties when conducting business due to the increased cost of living, inflation, and fluctuating exchange rate. The entrepreneurs’ views and perceptions of the government are generally negative, however, there are instances where the government is praised or viewed in a positive light.
Keywords: Small Business; Corruption; Economics, South Africa; Entrepreneurs